К вопросу о диагностировании состояния металлоконструкции углеперегружателя - Гусев, Ю. Б. (НТУ "ХПИ", 2007)
The method of diagnosing of the state of metalware of coal-loader is described in the paper. The research data are presented on the example of crane-loader made by FEB, FTA, Germany.
Keywords: комплекс исследования; кран-перегружатель; коррозионное поражение; акустическая эмиссия; техническое диагностирование; средства измерения